Working hours and common mental disorders in English police officers - Houdmont, Jonathan; Randall, Raymond (Oxford Journals, 2016)
Background: There is a paucity of evidence on working hours and their psychological correlates in police officers of the federated ranks in England. Aims: An exploratory study to establish the extent to which a sample of English police officers worked long hours and the association between long working hours and common mental disorder (CMD). Methods: Officers of the federated ranks (constable, sergeant, inspector) from two English county forces completed a questionnaire to report their typical weekly working hours and symptoms of CMD. We also collected socio- and occupational demographic data. We defined long working hours as ≥49 hours in a typical week in accordance with 48-hour weekly limit specified in the 1993 European Directive on the Organisation of Working Time. We established associations between long working hours and self-reported CMDs using binary logistic regression to generate ORs and 95% CIs adjusted for potential confounding variables. Results: 27% (N=327/1226) of respondents reported long working hours. The odds ratios for psychological distress (OR 2.05, 95% CI 1.57-2.68), emotional exhaustion (OR 1.99, 95% CI 1.52-2.59), and depersonalisation (OR 1.30, 95% CI 1.00-1.71) were significantly increased for long working hours after adjustment for socio- and occupational-demographic characteristics. Conclusions: More than one quarter of sampled police officers reported working long hours, and were significantly more likely to report CMD. National and longitudinal research is required to confirm these findings, which suggest management of working hours may effectively promote psychological wellbeing.